Phenomenological Research on Male Students' Perceptions as Victims of Sexual Harassment - farha, ghitsna nadila; Nur Eva; Fattah Hanurawan (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Sexual harassment of male university students is often overlooked in Indonesian higher education settings, where victims face social pressure, the stigma of masculinity, and fear of negative judgement. This study used a phenomenological approach to explore the subjective experiences of four male student victims of sexual harassment, focusing on its impact on identity and social interactions. Data were collected through in-depth interviews with four participants and analysed thematically. Experiences examined included unauthorised video-taking, authority-based harassment, physical pranks and verbal innuendos, and sexual harassment in dormitories. The analysis integrates hegemonic masculinity theory, social labelling theory, and victimhood awareness theory. Results showed that expectations of masculinity inhibited recognition of victim status, social labelling reinforced stigma, and lack of institutional support encouraged passive behaviour. This research recommends awareness raising, staff training, and supportive reporting mechanisms on campus.